PERBEDAAN PERILAKU MENYIKAT GIGI SISWA DALAM KESEHATAN GIGI DENGAN METODE STORYTELLING DI SDN 13 PARIT PUTUS KABUPATEN AGAM TAHUN 2018 - Harisnal, Harisnal (LPPM Universitas Muhammadiyah Sumatera Barat, 2018)
According to World Health Organization (WHO), 90% of school-aged children in the world havecaries in their teeth. Caries is caused by plaque and it can only be cleaned by brushing. Thecorrect technique of brushing behavior is based on the knowledge of the children. One of themethods that can be used in dental health education is storytelling. The purpose of this research isto know the difference of students tooth brushing behavior toward dental health education bystorytelling method at SDN 13 Parit Putus Agam Regency. Pre-experimental research design hadbeen used as the design of this research with one group pretest posttest design with threetreatments. The samples of this research were 20 people. It can be gotten from non-probabilitytechnique that was saturated sampling. The results of this research showed that the averagebehavior of tooth brushing students before being given dental health education trough storytellingmethod was 38.00. Meanwhile, after applying this method the average was around 45.15 with pvalue = 0.000. Of the three domains studied, the most significant change was knowledge, is aftertwo treatments, while the attitude domain on the third treatment and action domain had not showna very significant difference after three treatments. In conclusion, there is significant differencebetween tooth brushing behaviors on students before and after given dental health education bystorytelling method. It is suggested to health workers to apply this method in providing dentalhealth education to children in the school.Keywords : Storytelling, Brushing Behavior